Correlation between microstructure evolution and cryogenic fracture toughness in aging ITER-grade 316LN weldments. (December 2018) - Xin, Jijun; Fang, Chao; Huang, Chuanjun; Song, Yuntao; Wei, Jing; Li, Laifeng
Highlights: The 316LN austenitic stainless steel joints were PWHT at 760 °C for 1 h. The PWHT has no detrimental effect on the tensile strength of the joints. The fracture toughness of the weldments were investigated at cryogenic temperature. The fracture mechanism of the joints were evaluated. Abstract: In the present work, the correlation between microstructural evolution and fracture toughness in 316LN joints welded by Tungsten Inert Gas (TIG) was investigated. The effect of post-weld heat treatment (PWHT) on the microstructure and toughness was characterized. The welding process can significantly change the equiaxed grains of base metal to cells and dendrites, while the PWHT can increase the dendrite size, mitigate the texutre intensity, reduce the dislocation density, and slightly weaken the ultimate tensile strength of the joints. Fracture toughness tests reveal that the strain-induced martensitic transformation at cryogenic temperatures can remarkably deteriorate the fracture toughness. Due to the microstructural evolution during PWHT, the J-integral values at 77 K and 4.2 K decrese to 85% and 54% of those in the as-welded conditions, respectively. The fracture morphology of the as-welded joint shows a characterization of ductile fracture, while the PWHT joint features a mixture of ductile and brittle fracture.